2009
DOI: 10.1016/j.jcrs.2008.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis rates after implantation of the intraocular Collamer lens: Survey of users between 1998 and 2006

Abstract: An anonymous on-line survey was sent to 234 intraocular Collamer lens (ICL) (Staar Surgical) surgeons in 21 countries to determine how many of their ICL cases had been complicated by endophthalmitis between January 1998 and December 2006. A second questionnaire about the infection details and treatment outcome was sent to those who reported cases of endophthalmitis. Ninety-five (40%) surgeons responded to the survey. They had implanted 17954 ICLs during the study period. Three surgeons reported 1 case of endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Several studies report its effectiveness in correcting myopia, [1][2][3][4][5] hyperopia, 6,7 and astigmatism [8][9][10] or in patients who may not be appropriate candidates for corneal reshaping procedures. [11][12][13][14] However, in addition to the risks of any intraocular surgery, 15 the main concerns with pIOL implantation relate to its long-term safety, including long-term endothelial cell loss, 16,17 pigmentary glaucoma, 18 pupillary block, 19,20 and cataract formation. 21 Although studies of pIOL implantation report acceptable complication and visual acuity loss rates, few studies have spanned more than 3 years to observe the long-term clinical and refractive outcomes.…”
mentioning
confidence: 99%
“…Several studies report its effectiveness in correcting myopia, [1][2][3][4][5] hyperopia, 6,7 and astigmatism [8][9][10] or in patients who may not be appropriate candidates for corneal reshaping procedures. [11][12][13][14] However, in addition to the risks of any intraocular surgery, 15 the main concerns with pIOL implantation relate to its long-term safety, including long-term endothelial cell loss, 16,17 pigmentary glaucoma, 18 pupillary block, 19,20 and cataract formation. 21 Although studies of pIOL implantation report acceptable complication and visual acuity loss rates, few studies have spanned more than 3 years to observe the long-term clinical and refractive outcomes.…”
mentioning
confidence: 99%
“…Conservative management in mild cases, with intracameral or intravitreal antibiotics, may result in optimal visual recovery 2 8–10. However, a pars plana vitrectomy may be needed in more fulminant cases with poor visual and anatomical outcomes 4–6…”
Section: Discussionmentioning
confidence: 99%
“…Endophthalmitis is a potentially sight-threatening complication with an incidence of around 1 case per 6000 after posterior chamber phakic IOL implantation 2. The management is similar to postsurgical endophthalmitis; however, a phakic IOL explantation may additionally be required in cases with dismal visual outcomes 3–6…”
Section: Introductionmentioning
confidence: 99%
“…Allan et al [3] conducted an online survey of 234 surgeons in 21 countries to show how many of their ICL cases had been complicated by endophthalmitis between January 1998 and December 2006. During the study period, 3 surgeons reported 1 case of endophthalmitis each, a rate of 0.0167% or approximately 1 case of endophthalmitis per 6000 ICL implantations.…”
Section: Discussionmentioning
confidence: 99%